Prevalência da infecção latente por Mycobacterium tuberculosis nos transplantados renais - Monica Maria Delgado Maciel (2015)
Latency is the major obstacle to eradicating of Mycobacterium tuberculosis infections. Since immunosuppression might interfere with the outcome of the tuberculin skin test, detection of a latent to Mycobacterium tuberculosis infection is a big challenge. Latent to Mycobacterium tuberculosis infection treatment plays a fundamental role in renal transplantation, thereby avoiding dysfunction or loss of the graft. Preventive therapy may contribute to the reduction of potential cases of tuberculosis. This is a longitudinal study, which was conducted in outpatient clinic kidney transplants at the Hospital das Clinicas, Federal University of Minas Gerais, Brazil. In this study, 324 patients were selected and after applying the exclusion criteria and losses were evaluated 216 (66.7%) patients for latent to Mycobacterium tuberculosis infection using the tuberculin skin test. The recipients underwent renal transplantation from January 1978 to October 2010. Possible associations among risk factors and the response to tuberculin skin test were evaluated: gender, smoking history; past history of tuberculosis contact; body mass index; presence of Bacillus Calmette-Guérin scars; autoimmune disease; diabetes mellitus; presence of viral hepatitis and neoplasia after transplantation; immunosuppressive treatment; induction therapy; renal donor type; time interval between transplantation and the tuberculin skin test and renal function analysis at the time of tuberculin skin test. Recipients were divided into tuberculin skin test positive and negative groups; tuberculin test positive recipients received further preventive isoniazid treatment. A second tuberculin skin test had to be performed if the first was negative. Of the 216 patients, one hundred thirty-four patients (62%) were male, mean age of 46.5 years (SD ± 12.3). Diabetes mellitus was present in 25% of the patients. It was observed that the main cause of chronic kidney disease was unknown causes (50%), followed by glomerulopathy (22.2%). Univariate analysis showed no association among the presence of BCG scar, alcoholism, smoking, body mass index, Diabetes mellitus, immunosuppression regimen with different drug combinations, the interval between transplantation and tuberculin test with positive tuberculin skin test. Prior history of contact with tuberculosis and preserved renal function analyzed by glomerular filtration rate with values higher or equal to 60 mL/min/1,73m2 compared to the first tuberculin test, were significant. Therefore the prevalence of latent to Mycobacterium tuberculosis infection was 18.5% in this population. Among forty patients studied, twenty-nine (13.4%) of them were tested positive for the first tuberculin test and eleven (5.8%) were tested positive for a second test. The increment of the second test compared to the first was significant (p = 0.012). Prevalence of latent to Mycobacterium tuberculosis infection was low in kidney transplantation. There is an indication to perform a second tuberculin test when the first skin test is negative. Tuberculin skin test must be performed if there is better graft function.